2016
DOI: 10.1002/anie.201600654
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Distal Reactivity of Coumarins: A Rhodium‐Catalyzed Vinylogous Asymmetric Ring‐Opening Reaction

Abstract: While the utility of vinylogous enolates is well established in the setting of vinylogous aldol, Mannich, and Michael chemistries, literature reports concerning γ-reactivity are scarce for other reaction classes. Presented herein is an unprecedented example of vinylogous reactivity exemplified by the rhodium-catalyzed asymmetric ring-opening reaction of oxabicycles. This strategy also provides a powerful route to incorporate the biologically useful coumarin motif into the hydronapthalene scaffold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Lautens' group developed the first enantioselective γ-allylic alkylation of 4-methylcoumarins in 2016 through a Rh-catalyzed desymmetrizing ring-opening reaction of oxabicycles ( Scheme 2B ). 13 Very recently, our group 14 and subsequently Albrecht et al 15 independently developed the first organocatalytic enantioselective γ-allylic alkylation of 3-cyano-4-methylcoumarins using Morita–Baylis–Hillman carbonates as the allylic electrophile ( Scheme 2B ). While an excellent level of enantioselectivity has been achieved, the success of these reactions is inherently dependent on the type of allylic electrophile – both structurally and electronically, thereby limiting their scope.…”
Section: Introductionmentioning
confidence: 99%
“…Lautens' group developed the first enantioselective γ-allylic alkylation of 4-methylcoumarins in 2016 through a Rh-catalyzed desymmetrizing ring-opening reaction of oxabicycles ( Scheme 2B ). 13 Very recently, our group 14 and subsequently Albrecht et al 15 independently developed the first organocatalytic enantioselective γ-allylic alkylation of 3-cyano-4-methylcoumarins using Morita–Baylis–Hillman carbonates as the allylic electrophile ( Scheme 2B ). While an excellent level of enantioselectivity has been achieved, the success of these reactions is inherently dependent on the type of allylic electrophile – both structurally and electronically, thereby limiting their scope.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] However,t he use of g-nucleophiles in vinylogous propargylic substitution has not been explored, probably because of the difficulty to control the remote formation of bonds with high regioselectivity and enantioselectivity.Xie et al and Lautens et al independently demonstrated that cyanocoumarins can undergo vinylogous Michael addition and ring opening. [11] Thus,weenvisaged that cyanocoumarins might be viable substrates for vinylogous propargylic substitution reactions.H erein, we describe the first highly enantioselective copper-catalyzed vinylogous propargylic substitution and its application in the synthesis of an atural-product-inspired compound collection (Figure 1c).…”
mentioning
confidence: 99%
“…. ) are very often applied as catalyst precursors in homogeneous catalysis [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. These coordination compounds are usually not commercially available and must therefore be synthesized.…”
Section: In Situ Generation Of Precatalystsmentioning
confidence: 99%